On some problems of preparation specialists of higher qualification - Vasilij S. Senashenko (Высшее образование в России)
The paper discusses the key problems of preparation of specialists of higher qualification. The author draws attention to the fact that the conversion of postgraduate course into higher education educational program of the third level can be accompanied by the significant structural and conceptual changes in preparation of such specialists. The article emphasizes the complex character of the problem of scientific degree devaluation in modern Russia.